2006
DOI: 10.1002/cphc.200500695
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of the Asymmetric Stretch Vibration of CO2 in OH+CO→H+CO2 Reaction

Abstract: CO2vibrations: High excitation in the asymmetric stretch (v3) mode of the CO2 product in the OH+CO reaction has been found (see picture). The strong IR emission was detected by time‐resolved Fourier transform infrared (TR‐FTIR) emission spectroscopy. The observed vibrational distribution is used for comparison with a variety of theoretical calculations on this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
1
8
1
Order By: Relevance
“…However, no absorption from the (0,0,1) level (antisymmetric stretching) was detected. Shi et al reported significant excitation in the antisymmetric stretching mode of the CO 2 product . The limited CO 2 vibrational excitation observed in experiment of Frost et al is consistent with the translational distribution in the molecular beam experiment, which peaks near the highest accessible translational energy. , …”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, no absorption from the (0,0,1) level (antisymmetric stretching) was detected. Shi et al reported significant excitation in the antisymmetric stretching mode of the CO 2 product . The limited CO 2 vibrational excitation observed in experiment of Frost et al is consistent with the translational distribution in the molecular beam experiment, which peaks near the highest accessible translational energy. , …”
Section: Introductionmentioning
confidence: 53%
“…The dynamics of the reaction has also been investigated experimentally. Crossed molecular beam , and real-time measurements , indicated a relatively short lifetime for the HOCO intermediate. Translational energy distributions of the products suggested limited vibrational excitation in the CO 2 product, , although few state-resolved experiments have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…3(B) shows the in situ DRIFTS spectra while supplying NH 3 at 473 K. Peaks derived from NH 3 and N 2 species were also detected at around 3333, 1626, 1542 and 2178 cm –1 . 13 , 37 , 38 However, peaks assignable to the N–H vibrations derived from NH 4 + were very weak compared with those in Fig. 3(A) , even when applying the electric field.…”
Section: Resultsmentioning
confidence: 83%
“…Inelastic and reactive collisions of OH + CO were studied by crossed-molecular beam scattering [19][20][21] and transient FTIR spectroscopy. 22 The reverse reaction of H + CO 2 has been studied in van…”
Section: Kinetics Dynamics and Spectroscopymentioning
confidence: 99%